WAVE REFLECTION IS INVERSELY ASSOCIATED WITH THE DEVELOPMENT OF MYOCARDIAL HYPERTROPHY AMONG HYPERTENSIVE SUBJECTS. (June 2018) - Andreadis, E.; Kolyvas, G.; Geladari, C.; Georgantoni, A.; Savva, F.; Apeiranthiti, K.; Pantikidi, E.
Abstract : Objective: Wave reflection forms the basis of arterial input impedance and they offer valuable information on arterial stiffness. Thus, it has emerged as a strong, important marker of premature cardiovascular disease. Objective: To evaluate the association between wave reflection coefficient and the myocardial hypertrophy among hypertensive subjects. Design and method: Subjects with office blood pressure (BP) >140/90 mmHg, without treatment attending our Hypertension Center participated in the study. Exclusion criteria were renal dysfunction, heart failure, severe arrhythmia including atrial fibrillation and evidence of secondary hypertension. A complete medical history was obtained from all participants. Office BP was measured in 3 consecutive visits (Microlife WatchBPN, Microlife, Widnau, Switzerland). Consequently, all participants underwent 24 h ambulatory blood pressure monitoring (24h-ABPM), using the Mobil-O-Graph monitor (IEM, Stolberg, Germany). Mobil-O-Graph records oscillometric brachial BP, and calculates pulse wave velocity (PWV), aortic BP, augmentation index (Aix) and wave reflection as measure of arterial stiffness. BP measurements were performed at 20-min intervals for 24 hour. Daytime and nighttime periods were defined according to the patients' diaries (awake and asleep periods). Transthoracic echocardiogram for the assessment of myocardial hypertrophy was performed in all subjects. Results are expressed as frequencies and percentages for qualitative variables and as mean values with SD for quantitative variables. Statistical analysis was performed using the Student's t-test for independent samples. A p-value of 0.05 was considered statistically significant. Results: A total of 72 individuals, mean age 52.15 ± 11.97 years, 31 women were included in the analysis. A strong inversed association between wave reflection coefficient and myocardial hypertrophy was observed, with p values <0.002. Similar association were found for 24-hour, awake and asleep BP (p = 0.002, p = 0.018 and p = 0.002, respectively). Conclusions: Wave reflections markedly affect the central pressure profile, further contributing to increased cardiovascular risk. Future studies should assess the role of genetic versus geographic and other environmental influences in wave reflection coefficient as an index of vascular remodeling and especially aortic stiffness.